Association between chronic diseases, multimorbidity and insufficient physical activity among older adults in southern Brazil: a cross-sectional study - Gomes, Roselaine da Silva; Barbosa, Aline Rodrigues; Meneghini, Vandrize; Confortin, Susana Cararo; d’Orsi, Eleonora; Rech, Cassiano Ricardo (São Paulo Medical Journal, 2020)
BACKGROUND: Being active has been shown to have beneficial effects for the health of individuals with chronic diseases. However, data on the association between multimorbidity and physical activity are limited. OBJECTIVE: To investigate the association between chronic diseases, multimorbidity and insufficient physical activity among older adults in southern Brazil, according to sex. DESIGN AND SETTING: Cross-sectional population-based and household-based study derived from the second wave (2013-2014) of the EpiFloripa Aging Cohort Study. METHODS: Insufficiency of physical activity (outcome) was ascertained using the long version of the In- ternational Physical Activity Questionnaire (≤ 150 minutes/week). Eleven self-reported chronic diseases were identified. Multimorbidity was defined from the number of chronic diseases (none; 2 or 3; or 4 or more). The adjustment variables were age, schooling, marital status, income, smoking, alcohol consump- tion and cognition. Additionally, each chronic disease was adjusted for the others. Associations were test- ed using logistic regression (crude and adjusted). RESULTS: Among the 1197 participants (≥ 63 years), women (54.0%) were more likely than men (39.6%) to be insufficiently active. In the adjusted analysis, women and men with depressive symptoms, and men with diabetes, were more likely to be insufficiently active than those without symptoms. Multimorbid women were more likely to be insufficiently active, and the magnitude of the effect was strongest for 4 or more diseases. CONCLUSION: This study indicates that the associations were sex-specific. Depressive symptoms and multimorbidity were associated with insufficient physical activity among women, while diabetes was as- sociated with insufficient physical activity among men.